An Assessment of the Effectiveness of an Intervention to Quit Tobacco Use in Patients Seek Treatment from the Institute of Oral Health, Maharagama, Sri Lanka - Amarasinghe, Hemantha; Ananda, WFD; Hariachandra, SKD; Subashani, RADG; Wipularathna, KS; Nadira, ASF; Jayasinghe, Ruwan D (Asian Pacific Journal of Cancer Care, 2023)
Background: Tobacco is consumed in both smoked and smokeless forms. STEP Survey Sri Lanka 2015 showed that 29.4% males and 0.1% females were current smokers, Smokeless Tobacco (SLT) use was found in 26% of males and 5% of females. Dental setting could be considered as a suitable venue to provide brief health education message to persuade quit from tobacco. The aim of this study was to assess the effectiveness of brief intervention among tobacco users attending the Institute of Oral Health, Maharagama, Sri Lanka. Methods: Dental Surgeons provide routine care for the patients at the OPD and assess the use of tobacco at the beginning and help patients to quit tobacco which takes only 3-5 minutes. Method of intervention of this study is to provide brief messages to quit tobacco based on oral health effects due to tobacco use: staining teeth, status of periodontal health, halitosis, smoker’s keratosis, whiteness (burning) of the mucosa and palate and chewer’s mucosa. Tobacco quit rate and attempts were assessed through the telephone conversation in 3 months, 6 months intervals. Results: One hundred and twenty eighty subjects were recruited for the study, 45 (35%) failed to contact after 6 months interval which yielded the total sample of 83. Among 73 betel chewers, 46 (63%) subjects were completely quit the habit after 6 months. Eight out of 10 subjects who chew betel quid more than 5 quid per day quit. Among 22 smokers, 7 (32%) completely quit smoking with brief intervention at dental setting. Conclusion: Brief intervention at dental setting immensely helps to quit habit of daily betel chewers. This is an ongoing study relatively larger sample is needed for confirmation of the findings.